The Evaluation of Policy Implementation on ASN Performance Appraisal System - Shela Marlian; Widya Setiabudi Sumadinata; Deasy Silvya Sari (Universitas Padjadjaran, 2021)
Bandung Regency Government has implemented an information technology-based State Civil Servant (ASN) Performance Appraisal System, namely: Sabilulungan Employee Performance Appraisal System (SASIKAP) since 2018. This article aims to evaluate the implementation of SASIKAP in the last three years. The author uses the theory of policy implementation evaluation from William N. Dunn and qualitative methods for data collection and analysis. The results of this evaluation find that the implementation of SASIKAP policy has been effective; efficient; good enough in achieving goals and solving problems; rational alignment, responsive to developments, and appropriate in overcoming employee performance problems in Bandung Regency Government.